Efficiency Comparison of Asynchronous and Synchronous Buck Converter - Eraydin, Hasan; Bakan, A. Faruk (IEEE, 2020)
Switch mode power supplies depend on the principle of inductor energy transfer. At high frequency power density increases, magnetic elements in power electronics circuits become smaller. On the other hand, switching losses increase with frequency. Regulated low output voltage can be obtained by means of buck converter from a high voltage source. Traditionally a buck converter consists of a switch and a diode. In synchronous buck converter, diode is replaced with a MOSFET(Metal Oxide Semiconductor Field Effect Transistor). In this study, a 48 V input, 12 V and 4 A output buck converter is analysed. The power losses of semiconductor switches of buck converters are analysed with LTspice simulation software at different switching frequency values and different loads. Efficiency characteristics of asynchronous and synchronous buck converters are obtained. It is seen that efficiency depends on switching frequency and load conditions. Synchronous buck converter is more efficient than asynchronous buck converter in a wide operating range.
Keywords: buck converter; diode; synchronous rectification; asynchronous rectification; transistor; power electronics; Energy & Fuels; Engineering